E-Cigarette Use and Perceived Harm Among Women of Childbearing Age Who Reported Tobacco Use During the Past Year. Issue 5 (September 2016) - Ashford, Kristin; Wiggins, Amanda; Butler, Karen; Ickes, Melinda; Rayens, Mary Kay; Hahn, Ellen
Abstract : Background: The prevalence of electronic cigarette use grows. Amid increased e-cigarette use nationwide, this paper attempts to identify underlying risk factors for the most vulnerable populations. Objective: The purpose of the study was to assess predictors of e-cigarette use among female current and former tobacco users of childbearing age—specifically to determine whether demographic factors, pregnancy status, conventional cigarette smoking, and perceived e-cigarette harm are associated with e-cigarette use. Reasons for using e-cigarettes were also measured. Methods: A cross-sectional, correlational design was used; 194 current and former female tobacco users, 18–45 years of age, from two university-affiliated prenatal clinics and one women's health clinic in Kentucky took part. Slightly more than half were pregnant. Age, race/ethnicity, education, pregnancy status, use history for cigarettes and e-cigarettes, and perception of health hazard from e-cigarettes were measured, and associations with e-cigarette use were made with Mann–Whitney U -tests or Spearman's rank correlations. Predictors of e-cigarette use were determined using proportional odds modeling. Results: Most current e-cigarette users were also current cigarette smokers (88%). Nearly half of current and former e-cigarette users were pregnant. Most women perceived e-cigarettes as a minor (38%) or moderate (31%) health hazard. In the proportional odds model, younger women were at greater risk for e-cigarette use, whereas minority women and those who were pregnant were less likely to be e-cigarette users. Discussion: Pregnant women were less likely to be more recent e-cigarette users, compared with nonpregnant women. However, nearly all current e-cigarette users were dual tobacco users, including pregnant women. It is both imperative and timely to determine the impact of e-cigarette use on maternal and infant health, thus improving healthcare provider confidence to discuss the health implications of e-cigarette use with their patients.